2005
DOI: 10.1139/b05-018
|View full text |Cite
|
Sign up to set email alerts
|

Douglasdeweya: A new genus, with a new species and a new combination (Triticeae: Poaceae)

Abstract: The new genus Douglasdeweya C. Yen, J.L. Yang & B.R. Baum is based on results from cytogenetical and morphological findings — PPStSt genome — and is segregated from the genus Pseudoroegneria — StSt and StStStSt genome. Several characters, such as the erect spike with very finely spinulose pubescence along the two main angles of the rachis, and glumes and lemmas with a very strong midrib forming a keel-like structure distinguish Douglasdeweya from Pseudoroegneria, which has a rather lax spike, a rachis that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…For example, D. wangii 4 was included in the St and P clades; D. wangii 5 and 6 were grouped within the St clade; D. wangii 1, 2 and 3 were included in the P clade. These topologies indicated that ITSs in different D. wangii accessions showed a clear linkage with their related diploid ancestors, which further support the allotetraploid origin of D. wangii (Yen et al 2005;Baum and Johnson 2008). In addition, the ITS tree in this study also suggested a multiple origin of D. wangii resulting from recurrent hybridization, which can be shown by different accessions of the same species, will appear at different clades of a phylogenetic tree (Soltis and Soltis 1999).…”
Section: Phylogenetic Analysissupporting
confidence: 73%
See 2 more Smart Citations
“…For example, D. wangii 4 was included in the St and P clades; D. wangii 5 and 6 were grouped within the St clade; D. wangii 1, 2 and 3 were included in the P clade. These topologies indicated that ITSs in different D. wangii accessions showed a clear linkage with their related diploid ancestors, which further support the allotetraploid origin of D. wangii (Yen et al 2005;Baum and Johnson 2008). In addition, the ITS tree in this study also suggested a multiple origin of D. wangii resulting from recurrent hybridization, which can be shown by different accessions of the same species, will appear at different clades of a phylogenetic tree (Soltis and Soltis 1999).…”
Section: Phylogenetic Analysissupporting
confidence: 73%
“…It was originally included in Pseudoroegneria (Nevski) Á. Löve until recently when a new treatment was made by Yen et al (2005). Cytological data and molecular analysis of 5S rDNA sequences suggested that D. wangii has the StP genome composition, suggesting that the St genome was donated by the genus Pseudoroegneria and the P genome by the genus Agropyron (Yen et al 2005;Baum and Johnson 2008). However, hybrid speciation of D. wangii is still unknown.…”
Section: Communicated By K Schneitzmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytogenetic studies indicated that there are St, StSt, StP and E e St genomic constitutions in Pseudoroegneria and all of them are diploids or tetraploids (Dewey 1984;Wang et al 1986;Jensen et al 1992;Liu & Wang 1993). Yen et al (2005a) established a new genus Douglasdeweya C. Yen, J.L. Yang & B.R.…”
Section: Introductionmentioning
confidence: 99%
“…Thinopyrum, as treated here, includes species with just the E genome or both the E and the St genome. The latter species are sometimes placed in Trichopyrum (Löve 1986, Yen et al 2005.…”
Section: Genomic Compositionmentioning
confidence: 99%